The Problemic of the ambiguous relationship between the media and terrorism, and the problems arising from… An exploratory study of a sample of journalists, writers and researchers in Baghdad - Faraj Abdul-Hussein Al-Rubaie, Akram (ALBAHITH ALALAMI, 2021)
This study examined the problematic of the ambiguous relationship between the media and terrorism and the problems that result from press coverage of terroristic incidents. The paper sought to show the classification and confrontation of such incidents had been established from the point of view of a sample of media professionals, researchers and writers who are frequenters of Al-Mutanabi Street in Baghdad. The media outlets that carry this coverage would not give up their media mission as well as the terrorists would not be given an opportunity to take advantage of this coverage in achieving their goals and objectives. Furthermore, the terrorist organizations would have no chance to exploit these means to deliver their terroristic message. The researcher prepared a scale including several phrases to reveal the limits of the ambiguous relationship between the media and terrorism and the resulting problems that harm the reputation of the media institution, the citizen, and the society.